The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1159/000496734
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal Confounding in Randomized Controlled Trials of Antipsychotic, Antidepressant, and Stimulant Drugs, 2000–2017

Abstract: Background: Results of relapse prevention randomized controlled trials (RCTs) which discontinue psychotropic drug treatment from some participants may be confounded by drug withdrawal symptoms. We test for the confound by calculating whether ≥50% of the difference in relapse risk between drug-discontinued and drug-maintained groups is present at discontinuation time points (DCTs) with “short” and “long” assumptions regarding onset and duration of withdrawal symptoms. Methods: In eligible RCTs of antidepressant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…[74][75][76] Evaluating the conflicting evidence for antidepressants' longterm effectiveness, Hengartner concluded that "there is substantial withdrawal confounding in journals.sagepub.com/home/tpp discontinuation trials, which renders their findings uninterpretable" (p. 1). 69 In previous work systematically reviewing 80 discontinuation RCTs published since 2000, 20 70% with industry funding or participation, we found that, in most RCTs, most of the difference in relapse rates between drug-continued and drugdiscontinued groups occurred soon after discontinuation, 77 when withdrawal symptoms are most likely to occur. We identified several flaws in these trials.…”
Section: The Relapse-prevention Rct: Origins Uses and Biasesmentioning
confidence: 88%
“…[74][75][76] Evaluating the conflicting evidence for antidepressants' longterm effectiveness, Hengartner concluded that "there is substantial withdrawal confounding in journals.sagepub.com/home/tpp discontinuation trials, which renders their findings uninterpretable" (p. 1). 69 In previous work systematically reviewing 80 discontinuation RCTs published since 2000, 20 70% with industry funding or participation, we found that, in most RCTs, most of the difference in relapse rates between drug-continued and drugdiscontinued groups occurred soon after discontinuation, 77 when withdrawal symptoms are most likely to occur. We identified several flaws in these trials.…”
Section: The Relapse-prevention Rct: Origins Uses and Biasesmentioning
confidence: 88%
“…It is difficult to quantify the extent to which events recorded as depression relapse in maintenance studies are related to withdrawal reactions, but different estimations suggest that it is presumably the majority. 46,69,70 These findings indicate that there is substantial withdrawal confounding in relapse prevention (discontinuation) trials and that the internal validity of these studies is compromised. It follows that the results of these trials are uninterpretable.…”
Section: Discussionmentioning
confidence: 99%
“…Here, I will focus on one particular issue, that is, withdrawal confounding. 46 Various authors have stressed that prolonged antidepressant use can cause neurochemical adaptations (physical dependence) and corresponding withdrawal reactions upon dose reduction or discontinuation comparable with other central nervous system (CNS) drugs like benzodiazepines, stimulants or opioides. 18,22,47,48 There is now compelling evidence from clinical trials, observational studies and user surveys that stopping antidepressants can cause severe and persistent withdrawal reactions in a substantial portion of users.…”
Section: Withdrawal Confounding In Relapse Prevention Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Adverse clinical effects of discontinuing psychotropic drugs also can arise in changing from active drug to placebo in clinical trials. 6,7 Pharmacodynamic mechanisms underlying discontinuation syndromes…”
Section: Withdrawal Reactionsmentioning
confidence: 99%